(untitled) (Bangladesh Journal of Medical Science, 2010)
Introduction: Medical ethics means the moral principles, which should guide the members of the medical profession in the course of their practice of medicine and in relationship with their patients and other members of the profession. Objective: To recapitulate the matter to the medical practitioners so that they can apply them in course of their practice. Methodology: A search focused on the basic terminologies on medical ethics was made in Medline, PubMed and Cochrane database. The search captured citation on history of medical ethics. Both advances in medical ethics and advances in medicine and science with ethical ramifications were included. The topics span clinical medicine (end of life care and medical error), healthcare management (priority setting), science (biotechnology), and education (of medical ethics). Discussion & Conclusion: Core issues in in medical ethics: Autonomy, beneficence, non-malfeasance, justice – dignity, truthfulness and honesty. Different terms in the Field of Medical Ethics: Medical Etiquette, Professional infamous conduct, Professional death sentence, Professional secrecy, A physician should not commit any negligence or mal-practice. Islamic Medical Ethics: A Muslim physician derives his /her conclusion from rules of Islamic laws (Shariah). The goal of medical ethics is to improve the quality of patient care by identifying, analyzing, and attempting to resolve the ethical problems that arise in the practice of clinical medicine. Medical ethics is an important part of the undergraduate medical curriculum. It should not be left to a ’laissez-faire’ process of osmosis from teachers to students. DOI: 10.3329/bjms.v9i3.6467 Bangladesh Journal of Medical Science Vol.09 No.3 July 2010, pp.131-135